Intellectual disability and substance use/misuse: a narrative review. (14th March 2016) - Day, Christine; Lampraki, Alexandra; Ridings, Dean; Currell, Karen
Abstract : Purpose: – The purpose of this paper is to provide a narrative review of the literature on substance use/misuse within an intellectual disability (ID) population. The paper is focused on the prevalence, motivation and implications of substance use as well as the interventions for misuse. Design/methodology/approach: – Research focused on substance use and ID (IQ of 70 or less with onset in the developmental period) were considered. Findings: – The findings indicate a disparity between research findings regarding the prevalence of substance use/misuse within ID populations. Previous research indicates that individuals with ID may use/misuse substances as a form of relief or respite from negative experiences. Although there is a clear need for intervention, many of the ID population do not engage with generic interventions for substance misuse. Additionally, professionals responsible for the provision of interventions identify a lack of training and support to meet the needs of ID populations. Research limitations/implications: – Minimal research in this areas, barriers to language and demographics being underreported. Practical implications: – Highlights problems with the current evidence base and barriers this poses indicates a need for further research and intervention. Social implications: – Implications for the equality for individuals with an ID and their access to appropriate intervention. Focus on prevention of offending behaviour and intervention as appose to management. Originality/value: – In order to build a greater understanding of this issue, a shared universal language and definition of ID must be implemented. Further research to improve the understanding of why those with ID misuse substances is imperative before designing and implementing useful interventions.